Dementia-friendliness – Inclusion or exclusion: A critical discourse analysis. (August 2022) - Hansen, Tania EA; Andresen, Mette; Præstegaard, Jeanette; Tjørnhøj-Thomsen, Tine; Nørgaard, Birgitte
This article explores how individuals with dementia and their relatives discursively construct dementia-friendliness in a situation where different definitions of this term exists. Thirteen semi-structured interviews were conducted, including seven individual interviews with people living with dementia. The remaining six interviews consisted of three interviews with the relatives of a person with dementia and three with married couples of which one were diagnosed with dementia. Notes taken by the first author during 6 months of fieldwork at a day centre and a drop-in centre for people with dementia and their families were used to supplement the interviews. Critical discourse analysis provides an analytical tool for revealing the discourses constructing dementia-friendliness. The analysis revealed that people with dementia and their relatives draw on the three discourses of sameness, security and care and autonomy during their attempts to construct dementia-friendliness. The ensuing discursive battles over dementia-friendliness appear to constitute a tightrope walk between the inclusion and exclusion of people with dementia, which underscores the importance of including the voices of people living with dementia when dementia-friendly initiatives and communities are developed.